Method for preparing dry hydrogel material, use and method for preparing composite particulate material therewith
Patent Information
- Application Number
- CN202411172248.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-08-26
AI Technical Summary
虽然该方法可以实现实时制备,但是需要通过两级混合器,因此增加了制备工艺的复杂性,且在制备的产品中会含有未被固体疏水化材料包裹的液态水溶液,即不能100%形成干水状粉体,另外该方法仅适用于水溶液和固体疏水化材料
[0021] (1) The dry water-like material preparation method in this invention only requires one mixing, so the whole preparation process is simple and efficient and highly practical. At the same time, during the mixing process, the liquid is subjected to the dual shearing action of gas and solid powder, and the atomization effect is significant. From the implementation effect, the liquid can be 100% converted into dry water-like material with no liquid residue.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material preparation technology, specifically relating to a method for preparing a dry aqueous material, its application, and a method for preparing composite particulate materials using the same. Background Technology
[0002] Dry water-like materials are core-shell structured materials containing a liquid core and a solid outer shell, showing promising applications in gas storage, food, cosmetics, and fire extinguishing agents. Currently, the main preparation method for these materials is high-speed stirring, which is cumbersome and time-consuming. Chinese invention patent application CN202310605248.X discloses a real-time preparation method for dry water-like powder applicable to fire protection. This method uses compressed gas as a power source, first pre-mixing an aqueous solution and a solid hydrophobic material at a certain flow rate and proportion using a premixer, then dispersing and mixing them using a static mixer to ultimately form a cooling dry powder fire extinguishing agent. While this method allows for real-time preparation, it requires two stages of mixing, increasing the complexity of the process. Furthermore, the prepared product may contain liquid aqueous solution not encapsulated by the solid hydrophobic material, meaning it cannot form 100% dry water-like powder. Additionally, this method is only applicable to aqueous solutions and solid hydrophobic materials. Therefore, there is an urgent need to develop simpler and more efficient methods for preparing dry water-like materials and to expand the range of types of dry water-like materials. Summary of the Invention
[0003] To address the aforementioned problems, the present invention aims to provide a method for preparing a dry aqueous material, its application, and a method for preparing composite particulate materials using the same.
[0004] To achieve the above objectives, the method for preparing dry water-like materials provided by the present invention involves feeding liquid and solid powder into a dual-fluid atomizer at a certain flow rate for atomization and coating, thereby forming a dry water-like material in which solid powder coats small liquid droplets.
[0005] The liquid includes hydrophilic liquids and hydrophobic-oleophobic liquids, wherein the hydrophilic liquid is selected from at least one of water, aqueous inorganic salt solution, alcohol solution and carboxylic acid solution; the hydrophobic-oleophobic liquid is selected from at least one of fluorinated alkane solution, fluorinated olefin solution, fluorinated cyclic compound solution and fluorinated ketone compound solution; if the above solution contains a solute, the mass concentration of the solute is from 0.1% to its saturation mass concentration.
[0006] The inorganic salt aqueous solution is selected from at least one of the following: ammonium dihydrogen phosphate aqueous solution, ammonium polyphosphate aqueous solution, urea aqueous solution, sodium dihydrogen phosphate aqueous solution, potassium bicarbonate aqueous solution, sodium bicarbonate aqueous solution, sodium carbonate aqueous solution, potassium carbonate aqueous solution, sodium chloride aqueous solution, potassium chloride aqueous solution, ammonium bromide aqueous solution, ammonium sulfate aqueous solution, ammonium bisulfate aqueous solution, aluminum ammonium sulfate aqueous solution, sodium borate aqueous solution, potassium ferricyanide aqueous solution, lanthanum nitrate aqueous solution, lanthanum sulfate aqueous solution, lanthanum carbonate aqueous solution, lanthanum phosphate aqueous solution, cerium nitrate aqueous solution, cerium sulfate aqueous solution, cerium carbonate aqueous solution, cerium phosphate aqueous solution, yttrium nitrate aqueous solution, yttrium sulfate aqueous solution, yttrium carbonate aqueous solution, and yttrium phosphate aqueous solution.
[0007] The alcohol solution is selected from at least one of methanol solution, ethanol solution, isopropanol solution, n-butanol solution, isopentylene glycol solution, n-hexanol solution, and hexafluoroisopropanol solution;
[0008] The carboxylic acid solution is selected from at least one of oxalic acid solution, trifluoroacetic acid solution, propionic acid solution, and oxalic acid solution;
[0009] The fluorinated alkane solution is selected from at least one of perfluoro-2-methylpentane solution, perfluorohexane solution, and 1,1,1,2,3,4,4,5,5,5-decafluoropentane solution;
[0010] The fluorinated olefin solution is selected from at least one of 2-bromo-3,3,3-trifluoropropene solution, 1,1,1,4,4,4-hexafluoro-2-butene solution, and 3,3,4,4,5,5-hexafluorocyclopentene solution;
[0011] The fluorinated cyclic compound solution is selected from at least one of 1,1,2,2,3,3,4-heptafluorocyclopentane solution, 1,1,2,2,3,3,4,5-octafluorocyclopentane solution, and perfluorocyclohexane solution;
[0012] The fluorinated ketone compound solution is selected from at least one of perfluorohexanone solution, perfluoropentanone solution, and perfluorobutanone solution.
[0013] The solid powder includes inorganic hydrophobic powder and organic polymer powder, wherein the inorganic hydrophobic powder is selected from at least one of fluorinated carbon powder, hydrophobic silica powder, hydrophobic ceramic powder, hydrophobic metal oxide powder, hydrophobic hollow glass microsphere powder, and hydrophobic sparingly soluble salt powder; the organic polymer powder is selected from at least one of polyvinyl alcohol powder, epoxy resin powder, polyacrylamide powder, and carboxymethyl cellulose; and the particle size of the solid powder is less than or equal to 100 micrometers.
[0014] The mass ratio of the liquid to the solid powder is 99-50:1-50.
[0015] The concentration of the solid powder during flow is controlled by a quantitative powder aerosolization technique. The method involves placing the solid powder in a container with a variable volume, then introducing a low-boiling-point gas at a certain flow rate as a driving gas to form an aerosol state. The resulting aerosol solid powder is then fed into a two-fluid atomizer. Simultaneously, as the mass of the solid powder in the container decreases, the container volume gradually shrinks to ensure that the output solid powder concentration remains constant. The flow of the liquid is driven by the siphon effect of the two-fluid atomizer.
[0016] The low-boiling-point gas is selected from at least one of compressed nitrogen, compressed air, compressed carbon dioxide, liquefied heptafluoropropane, liquefied hexafluoropropane, liquefied trifluoroiodomethane, liquefied octafluoropropane, liquefied pentafluoroethane, liquefied tetrafluoroethane, and liquefied trifluoromethane.
[0017] The dual-fluid atomizer is selected from at least one of the following: bubble atomizer, jet atomizer, whistle atomizer, dual-fluid impact atomizer, external mixing airflow atomizer, internal mixing airflow atomizer, internal and external mixing combined airflow atomizer, Y-type airflow atomizer, hydrodynamic ultrasonic atomizer, dual-fluid electrostatic atomizer, and two-phase flow centrifugal atomizer.
[0018] The dry, watery material is used to extinguish battery fires, solid fires, liquid fires, and flammable gas fires.
[0019] The method for preparing surface-coated composite particle materials using the aforementioned dry aqueous material provided by the present invention is to dry the dry aqueous material by freeze-drying or heating to remove the solvent in the dry aqueous material, thereby forming a core-shell surface-coated composite particle material.
[0020] Compared with the prior art, the method of the present invention has the following beneficial effects:
[0021] (1) The dry water-like material preparation method in this invention only requires one mixing, so the whole preparation process is simple and efficient and highly practical. At the same time, during the mixing process, the liquid is subjected to the dual shearing action of gas and solid powder, and the atomization effect is significant. From the implementation effect, the liquid can be 100% converted into dry water-like material with no liquid residue.
[0022] (2) This invention can be used to prepare dry water-like materials that are not aqueous solutions, for example, to prepare microcapsule-type fire extinguishing agents with perfluorohexanone as the liquid core, thus having a wider range of applications.
[0023] (3) The dry water-like material prepared by the present invention can be used directly for fire extinguishing. It can achieve ultra-low temperature cooling effect through driving gas regulation, and has stronger fire extinguishing and cooling capabilities. It is suitable for fires with high cooling requirements, such as battery fires.
[0024] (4) The present invention also provides a method for directly preparing core-shell surface-coated composite particle materials from dry watery materials. This method can be used for the preparation of cold aerosol fire extinguishing agents, solving the problem of easy agglomeration in the preparation of traditional cold aerosol fire extinguishing agents. At the same time, the density and particle size of cold aerosol fire extinguishing agents can be controlled by controlling the drying method. Detailed Implementation
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Example 1
[0027] First, place 200 mL of a 20% (w / w) ammonium dihydrogen phosphate aqueous solution into a storage tank, with a specific surface area of 200 m². 2 10g of hydrophobic silica powder (at a concentration of 5mg / cm³) was placed as a solid powder in a compressible powder storage tank. Then, the air inlet of an internal mixing atomizer was connected to the compressible powder storage tank, and the liquid inlet was connected to a liquid storage tank. The compressible powder storage tank was also connected to a compressed nitrogen cylinder. Finally, the air inlet pressure of the compressible powder storage tank was adjusted to 0.4MPa and the valve was opened. Under the pressure of the compressed nitrogen, the hydrophobic silica powder formed a flow rate of 400mL / min and a concentration of 5mg / cm³. 3 The aerosol gas enters the internal mixing airflow atomizer and generates a siphon effect. Under this effect, the ammonium dihydrogen phosphate aqueous solution enters the internal mixing airflow atomizer at a flow rate of 100 g / min for atomization, and finally forms a dry water-like material with the ammonium dihydrogen phosphate aqueous solution as the liquid core and hydrophobic silica as the solid shell.
[0028] Tests showed that the conversion rate of ammonium dihydrogen phosphate aqueous solution to dry aqueous material was 100%, with no liquid residue. The D90 particle size of the dry aqueous material was 22 micrometers, and the density was 0.83 g / cm³. 3 The liquid core content reaches 98% (by mass).
[0029] Using this technology, the prepared dry water-like material was directly sprayed as a fire extinguishing agent onto a heated 200Ah lithium-ion battery in real time. The test results showed that the open flame could be extinguished within 6 seconds, the battery surface temperature could be reduced to 78°C, and the battery did not reignite.
[0030] Example 2
[0031] First, place 200 mL of a 20% urea aqueous solution into a storage tank, with a specific surface area of 200 m². 210g of hydrophobic alumina powder (at a concentration of 5mg / cm³) was placed as a solid powder in a compressible powder storage tank. Then, the air inlet of an external mixing atomizer was connected to the compressible powder storage tank, and the liquid inlet was connected to a liquid storage tank. The compressible powder storage tank was also connected to a liquefied heptafluoropropane cylinder. Finally, the air inlet pressure of the compressible powder storage tank was adjusted to 0.4MPa and the valve was opened. Under the pressure of the heptafluoropropane, the hydrophobic alumina powder formed a flow rate of 400mL / min and a concentration of 5mg / cm³. 3 The aerosol gas enters the external mixing airflow atomizer and generates a siphon effect. Under this effect, the urea aqueous solution enters the external mixing airflow atomizer at a flow rate of 100 g / min for atomization, forming a dry water-like material with urea aqueous solution as the liquid core and hydrophobic alumina as the solid shell.
[0032] Tests showed that the conversion rate of urea aqueous solution to dry aqueous material was 100%, with no liquid residue. The D90 particle size of the dry aqueous material was 16 micrometers, and the density was 0.9 g / cm³. 3 The liquid core content reaches 97% (by mass).
[0033] This technology allows for the direct application of a prepared dry, water-like material as a fire extinguishing agent to a heated 200Ah lithium-ion battery in real-time. Experimental results show that the fire can be extinguished within 3 seconds, the battery surface temperature can be reduced to 6°C, and the battery did not reignite. It can be seen that this embodiment has a better cooling effect than Example 1. This is because low-boiling-point liquefied heptafluoropropane is used as the driving gas. During mixing in the mixer, the liquid heptafluoropropane vaporizes and absorbs heat, resulting in a low-temperature effect. The prepared dry, water-like material has a lower temperature (tested at -12°C at the mixer nozzle), thus providing a better cooling effect when extinguishing lithium battery fires.
[0034] Example 3
[0035] First, place 200 mL of a 10% ammonium polyphosphate aqueous solution into a storage tank, with a specific surface area of 220 m². 2 10g of hydrophobic hollow glass microsphere powder (approximately 0.5g / g) was placed as a solid powder in a compressible powder storage tank. Then, the air inlet of a Y-type atomizer was connected to the compressible powder storage tank, and the liquid inlet was connected to a liquid storage tank. The compressible powder storage tank was also connected to a carbon dioxide cylinder. Finally, the air inlet pressure of the compressible powder storage tank was adjusted to 0.4MPa and the valve was opened. Under the pressure of carbon dioxide gas, the hydrophobic hollow glass microsphere powder formed a flow rate of 400mL / min and a concentration of 5mg / cm³. 3The aerosol gas enters the Y-type airflow atomizer and generates a siphon effect. Under this effect, the ammonium polyphosphate aqueous solution enters the Y-type airflow atomizer at a flow rate of 100 g / min for atomization, forming a dry water-like material with the ammonium polyphosphate aqueous solution as the liquid core and the hydrophobic hollow glass microsphere powder as the solid shell.
[0036] Testing showed that the conversion rate of ammonium polyphosphate aqueous solution to dry aqueous material was 100%, with no liquid residue. The D90 particle size of the dry aqueous material was 33 micrometers, and the density was 0.2 g / cm³. 3 The liquid core content reaches 96% (by mass).
[0037] This technology was used to directly spray the prepared dry, water-like material as an extinguishing agent onto an oil pan fire (fuel: n-heptane, oil pan diameter: 920 mm) in real-time. Experimental results showed that the flames could be extinguished within 4 seconds, and the dry, water-like material could cover the entire surface of the liquid fuel, effectively smothering it and preventing reignition. This demonstrates that using a low-density, hollow-structured solid powder as the outer shell of the dry, water-like material can effectively reduce its density, allowing it to float on the surface of the liquid fuel, thus making it suitable for extinguishing liquid fires.
[0038] Example 4
[0039] First, 200 mL of perfluorohexanone solution containing 1% ethylenediamine (mass concentration) was placed in a storage tank. 20 g of bisphenol A epoxy resin powder was placed in a compressible powder storage tank as the solid powder. Then, the air inlet of the internal / external mixing atomizer was connected to the compressible powder storage tank, and the liquid inlet was also connected to the storage tank. The compressible powder storage tank was also connected to a compressed nitrogen cylinder. Finally, the air inlet pressure of the compressible powder storage tank was adjusted to 0.35 MPa and the valve was opened. Under the pressure of nitrogen, the bisphenol A epoxy resin powder formed a flow rate of 320 mL / min and a concentration of 10 mg / cm³. 3 The aerosol gas enters the internal and external mixed airflow atomizer and generates a siphon effect. Under this effect, the ethylenediamine perfluorohexanone solution enters the internal and external mixed airflow atomizer at a flow rate of 90 g / min for atomization, forming a dry water-like material with the ethylenediamine perfluorohexanone solution as the liquid core and bisphenol A type epoxy resin powder as the solid shell.
[0040] Testing showed that the conversion rate of the ethylenediamine perfluorohexanone solution to a dry aqueous material was 100%, with no liquid residue. The D90 particle size of the dry aqueous material was 89 micrometers, and the liquid core content reached 95% (by mass). When this dry aqueous material was left to stand at 35°C for 24 hours, it formed a microcapsule fire extinguishing agent containing perfluorohexanone. The principle is that the ethylenediamine in the liquid core perfluorohexanone solution promotes the cross-linking reaction of the outer bisphenol A type epoxy resin, thereby forming a capsule structure. This example demonstrates that the present invention can be used for the preparation of non-aqueous dry aqueous materials, and that a microcapsule structure can be formed by adjusting the reaction between the solute in the liquid core solution and the outer encapsulating material.
[0041] Example 5
[0042] First, place 200 mL of a 16% potassium bicarbonate aqueous solution into a storage tank, with a specific surface area of 400 m². 2 10g of hydrophobic ceramic powder (at a concentration of 5mg / cm³) was placed as a solid powder in a compressible powder storage tank. Then, the air inlet of a two-phase flow centrifugal atomizer was connected to the compressible powder storage tank, and the liquid inlet was connected to a liquid storage tank. The compressible powder storage tank was also connected to a compressed nitrogen cylinder. Finally, the air inlet pressure of the compressible powder storage tank was adjusted to 0.4MPa and the valve was opened. Under the pressure of the compressed nitrogen, the hydrophobic ceramic powder formed a flow rate of 400mL / min and a concentration of 5mg / cm³. 3 The aerosol gas enters the two-phase flow centrifugal atomizer and generates a siphon effect. Under this effect, the potassium bicarbonate aqueous solution enters the internal and external mixed airflow atomizer at a flow rate of 100 g / min for atomization, forming a dry water-like material with potassium bicarbonate aqueous solution as the liquid core and hydrophobic ceramic powder as the solid shell.
[0043] Tests showed that the conversion rate of potassium bicarbonate aqueous solution to dry aqueous material was 100%, with no liquid residue. The D90 particle size of the dry aqueous material was 10 micrometers, and the density was 0.81 g / cm³. 3 The liquid core content reaches 98% (by mass).
[0044] 10g of the dried aqueous material was placed in a freeze dryer at -18℃ and vacuum dried for 48 hours to remove the solvent, ultimately forming a core-shell composite particle material of potassium bicarbonate encapsulated in hydrophobic ceramic powder. Testing showed that the composite material had a D90 particle size of 8 micrometers, no agglomeration, a deionized water contact angle of 123°, a flowability index of 0.171 (vibration test), a moisture absorption rate of 0.2%, a bulk density of 0.38 g / mL, and a Class B fire extinguishing efficiency of 56 g / m³. 3This indicates that the hydrophobic potassium bicarbonate powder prepared by this method has small particle size, good hydrophobicity, good flowability, and high fire extinguishing efficiency. It solves the problem of easy agglomeration and poor hydrophobicity in dry powder fire extinguishing agents prepared by traditional methods of modifying silicone oil followed by mechanical pulverization. This method is applicable to the preparation of cold aerosol fire extinguishing agents, offering not only good results but also convenient operation and a simple process.
[0045] Example 6
[0046] First, place 200 mL of a 16% potassium bicarbonate aqueous solution into a storage tank, with a specific surface area of 400 m². 2 10g of hydrophobic ceramic powder (at a concentration of 5mg / cm³) was placed as a solid powder in a compressible powder storage tank. Then, the air inlet of a two-phase flow centrifugal atomizer was connected to the compressible powder storage tank, and the liquid inlet was connected to a liquid storage tank. The compressible powder storage tank was also connected to a compressed nitrogen cylinder. Finally, the air inlet pressure of the compressible powder storage tank was adjusted to 0.4MPa and the valve was opened. Under the pressure of the compressed nitrogen, the hydrophobic ceramic powder formed a flow rate of 400mL / min and a concentration of 5mg / cm³. 3 The aerosol gas enters the two-phase flow centrifugal atomizer and generates a siphon effect. Under this effect, the potassium bicarbonate aqueous solution enters the two-phase flow centrifugal atomizer at a flow rate of 100 g / min for atomization, forming a dry water-like material with potassium bicarbonate aqueous solution as the liquid core and hydrophobic ceramic powder as the solid shell.
[0047] Tests showed that the conversion rate of potassium bicarbonate aqueous solution to dry aqueous material was 100%, with no liquid residue. The D90 particle size of the dry aqueous material was 10 micrometers, and the density was 0.81 g / cm³. 3 The liquid core content reaches 98% (by mass).
[0048] 10g of the dried, watery material was placed in a heating chamber at 60℃ and dried for 8 hours to remove the solvent, ultimately forming a core-shell composite granular material of potassium bicarbonate encapsulated in hydrophobic ceramic powder. Testing showed that the composite granular material had a D90 particle size of 3 micrometers, no agglomeration, a deionized water contact angle of 123°, a flowability index of 0.171 (vibration test), a moisture absorption rate of 0.3%, a bulk density of 0.38 g / mL, and a Class B fire extinguishing efficiency of 56 g / m³. 3 This indicates that the core-shell composite particles of potassium bicarbonate encapsulated in hydrophobic ceramic powder prepared by this method have small particle size, good hydrophobicity, good flowability, and high fire extinguishing efficiency. It solves the problem of easy agglomeration and poor hydrophobicity in dry powder fire extinguishing agents prepared by traditional methods of modifying silicone oil followed by mechanical pulverization. This method is applicable to the preparation of cold aerosol fire extinguishing agents, offering not only good results but also convenient operation and a simple process.
[0049] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on its differences from other embodiments. Similar or identical parts between embodiments can be referred to interchangeably. For the apparatus disclosed in the embodiments, since they correspond to the methods disclosed in the embodiments, the description is relatively simple; relevant parts can be referred to the method section.
[0050] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a dry aqueous material, wherein the method involves feeding liquid and solid powder into a dual-fluid atomizer at a certain flow rate for atomization and coating, thereby forming a dry aqueous material in which solid powder coats small liquid droplets; characterized in that: The concentration of the solid powder during flow is controlled by a quantitative powder aerosolization technique. The method involves placing the solid powder in a container with a variable volume, then introducing a low-boiling-point gas at a certain flow rate as a driving gas to form an aerosol state. The resulting aerosol solid powder is then fed into a two-fluid atomizer. Simultaneously, as the mass of the solid powder in the container decreases, the container volume gradually shrinks to ensure that the output solid powder concentration remains constant. The flow of the liquid is driven by the siphon effect of the two-fluid atomizer.
2. The method for preparing a dry aqueous material according to claim 1, characterized in that: The low-boiling-point gas is selected from at least one of compressed nitrogen, compressed air, compressed carbon dioxide, liquefied heptafluoropropane, liquefied hexafluoropropane, liquefied trifluoroiodomethane, liquefied octafluoropropane, liquefied pentafluoroethane, liquefied tetrafluoroethane, and liquefied trifluoromethane.
Citation Information
Patent Citations
A cooling type dry powder fire extinguishing agent and its preparation method and application
CN116474306B
Perovskite quantum dot composite material and preparation method and application thereof
CN115717071A